The Ubiquitous Conserved Glycopeptidase Gcp Prevents Accumulation of Toxic Glycated Proteins - Chen Katz; Ifat Cohen-Or; Uri Gophna; Eliora Z. Ron (mBio, 2010)
ABSTRACT Amadori-modified proteins (AMPs) are the products of nonenzymatic glycation formed by reaction of reducing sugars with primary amine-containing amino acids and can develop into advanced glycated end products (AGEs), highly stable toxic compounds. AGEs are known to participate in many age-related human diseases, including cardiovascular, neurological, and liver diseases. The metabolism of these glycated proteins is not yet understood, and the mechanisms that reduce their accumulation are not known so far. Here, we show for Escherichia coli that a conserved glycopeptidase (Gcp, also called Kae1), which is encoded by nearly every sequenced genome in the three domains of life, prevents the accumulation of Amadori products and AGEs. Using mutants, we show that Gcp depletion results in accumulation of AMPs and eventually leads to the accumulation of AGEs. We demonstrate that Gcp binds to glycated proteins, including pyruvate dehydrogenase, previously shown to be a glycation-prone enzyme. Our experiments also show that the severe phenotype of Gcp depletion can be relieved under conditions of low intracellular glycation. As glycated proteins are ubiquitous, the involvement of Gcp in the metabolism of AMPs and AGEs is likely to have been conserved in evolution, suggesting a universal involvement of Gcp in cellular aging and explaining the essentiality of Gcp in many organisms. IMPORTANCE Glycated proteins (Amadori-modified proteins [AMPs] and advanced glycated end products [AGEs]) are known to participate in many age-related diseases. Their existence in fast-growing organisms was considered unlikely, as their formation was assumed to be slow. Yet, recent evidence demonstrated their existence in bacteria, and our data suggest a bacterial mechanism that reduced their accumulation. We identify in Escherichia coli a protein, Gcp, which carries out this function. Gcp is conserved in all domains of life and is essential in many organisms. Although it was annotated as a chaperon protease, there were no experimental data to support this function. Our findings are compatible with the annotation and will open up studies of the bacterial metabolism of glycated proteins. Furthermore, the data from the bacterial systems may also be instrumental in understanding the metabolism of glycated proteins, including their toxicity in human health and disease.